The impact of the Covid-19 Pandemic on earnings management - Evidence from listed companies in China - Du, Anqi (2022)
The Covid-19 pandemic and the ensuing recession have caught many firms off-guard, posing an existential threat to the viability of some businesses, which in turn has had a significant impact on the financial reports of enterprises. The aim of this study is to determine the impact of the Covid-19 pandemic on earnings management practices. This study uses a sample including 1,832 listed companies in China for a period from 2015 to 2020. To capture earnings management, this paper uses the Modified Jones model to measure accrual-based earnings management (Dechow et al., 1995), and real activity-based earnings management is measured by the sum of the absolute values of the abnormal production costs, the abnormal cash flow from operations, and the abnormal discretionary expenditures (Cohen et al., 2008; Roychowdhury, 2006). The results show that the sample companies are more inclined to manipulate earnings during the pandemic period than in the prior time. This finding implies that financial reporting is less reliable during the Covid-19 pandemic. The further investigation provides proof of significant income-increasing earnings management during the pandemic period. This finding shows that companies manage earnings upward by mitigating reported losses to a level acceptable to stakeholders in order to attract investors without losing existing ones, thereby supporting economic recovery. In addition, this article finds that financially distressed firms are more inclined to adopt earnings manipulation, especially accrual-based earnings management.